Heterogeneity of triglyceride-rich lipoproteins in the postprandial state - Karpe, F (1999)
Triglyceride-rich lipoproteins in plasma are a heterogenous population of apolipoprotein B containing lipoproteins in plasma. After liberation of the esterified fatty acids by lipoprotein lipase, the non-esterified fatty acids provide a major source of energy, either used immediately in muscle or for storage in adipose tissue. Hypertriglyceridemia is a sign of an imbalanced system and implicated in disease processes such as atherosclerosis and impaired fibrinolysis. Levels and composition of triglyceride-rich liproteins are undergoing marked fluctuations during the day, depending on metabolic status. The present review deals with the principle regulatory mechanisms of the system in the postprandial state with a special reference to insulin-mediated mechanisms.